Developing clinical expertise in musculoskeletal physiotherapy; Using observed practice to create a valued practice-based collaborative learning cycle. (December 2020) - Carr, Matthew; Morris, Jane; Kersten, Paula
Abstract: Background: Observed clinical practice is a commonly used approach to develop clinical expertise in the musculoskeletal (MSK) physiotherapy workforce. The value of this approach is not known. Objectives: To understand how regular observed clinical practice is considered to support the development of MSK physiotherapy clinical expertise in one UK organisation who adopts this approach to practice-based education. Design: A qualitative, constructivist grounded theory study. Method: Eight initial individual interviews were undertaken with MSK physiotherapists engaged in this approach to practice-based education. Secondary interviews were completed with two participants. A focus group concluded data generation. Data were analysed using a three-stage constant comparative process. Findings: Regular observed clinical practice was found to facilitate the development of clinical expertise by enabling a valued practice-based collaborative learning cycle. Three essential elements were identified: Precursory requirements: Mentors are required to reflect on their own successful experiences of clinical development and consider their professional moral responsibility to develop the future workforce. Learning activity: Observed clinical practice situated in the workplace can successfully facilitate clinical expertise development. Whole-team involvement adds further value. Subsequent requirements: Successful learning outcomes are achieved when mentor and learner engage in collaborative reflection and analysis soon after the observed practice. Developing an 'educational alliance', sharing fallibilities, adopting a developmental approach and placing the learner as the 'judge' of the learning experience are important considerations to achieve successful learning outcomes. Conclusion: These findings offer a framework to consider when using observed clinical practice to develop the clinical expertise of a MSK physiotherapy workforce. Highlights: Clinical expertise is facilitated using a valued practice-based collaborative learning cycle. Observed practice with subsequent reflection and analysis supports clinical expertise development. A valued collaborative learning cycle requires a self-reflective, facilitative mentor. Whole-team involvement is beneficial to a valued collaborative learning cycle. A 'learning community of practice' facilitates this approach.